Microwave-Assisted Extraction of Organic Compounds from Yanan Coal at Room Temperature - Liu, T.; Peng, Y.L.; Hou, J.H. (Asian Journal of Chemistry, 2014)
Yanan coal was sequentially extracted with petroleum ether, carbon disulfide, methanol and acetone at room temperature under microwave irradiation condition, affording extracts 1 to 4 (F1 to F4). In total, 105 organic compounds were identified from yanan coal by gas chromatography/mass spectrometry analysis, especially, 60 organic compounds were detected in carbon disulfide extracts (F2). The organic compounds include 17 alcohols, 19 esters, 23 arenes, 9 acids, 8 heteroatom-containing organic compounds, 5 aldehydes, 5 ketones, 2 organic iodines and other organic compounds. The experiment provides an essential and effective approach investigations of coal composition and structure in separable and nondestructive methods.